Analysis of Mathematical Creative Thinking Ability in View of Students' Confidence in Number Pattern Material - Nurhidayati, Farida; Abadi, Agus Maman (International Journal of Scientific Research and Management (IJSRM), 2024)
In the 21st century, learning mathematics requires students to master 4 skills, one of which is creative mathematical thinking. This ability will encourage students to have different points of view in solving a problem. The low ability to think creatively in mathematics is shown by the large number of students who are unable to express creative ideas when studying mathematics. One of the things that underlies creativity is self-confidence because there is a relationship between the two. The aim of this research is to describe mathematical creative thinking abilities in terms of self-confidence in number pattern material. This research is descriptive qualitative research. The subjects in this research were 6 students with high, medium and low self-confidence categories in each class VIII A and VIII B. The data collection techniques used were questionnaires, tests and interviews and analyzed using triangulation of sources and techniques. Apart from that, there are 3 stages of data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The research results show that students with high self-confidence have a level of creative thinking ability (TKBK) 4 (very creative) by mastering the indicators of fluency, flexibility and novelty. Then students with moderate self-confidence have a creative thinking ability level (TKBK) 3 (creative) by mastering fluency and flexibility indicators. Finally, students with low self-confidence have a creative thinking ability level (TKBK) 3 (creative) by mastering indicators of fluency and flexibility.